FACIES AND DEPOSITIONAL ENVIRONMENT ANALYSIS OF TELISA FORMATION, BRAVO FIELD, CENTRAL SUMATRA BASIN, RIAU, INDONESIA - GAFUR , ABDURRAHMAN
Balam Trough is one of sub basin in the north part Central Sumatra Basin, Riau, which is owned by PT. Chevron Pacific Indonesia. This research was carried out on the Bravo Field is located in the east sub basin. This research has been investigated in 4 reservoir intervals from Duri_Sand_A – T_A_FS4 located in 155 wells within an area of ± 148.5 km2. The objective of this research is to determine facies distribution by doing subsurface mapping and estimate the geometry of facies in reservoir intervals. Based on biostratigraphy analysis and stratigraphy correlation, reservoirs in Duri_Sand_A – T_A_FS4 interval were deposited about 20 million years ago in Early – Middle Miocene and they can be found across the Balam Trough area. Core analysis shows that four reservoir intervals have 13 lithofacies consisted of 10 sandstone lithofacies and 3 claystone-siltstone lithofacies. Sandstone lithofacies consists of dari Snr, Sps, Sr, Sl, Spb, Sc, Ssm, Sm, Slmb, dan Slb. Claystonesiltstone lithofacies consists of Fs, Fm, and Fc. The depositional environment of the entire interval is a tide dominated estuary (intertidal to subtidal) and it is divided into 4 facies association. They are estuarine channel, intertidal sand bar, subtidal channel, dan sandy mud flat. Based on chronostratigraphy correlation and seismic 3D interpretation, the estimated result of distribution and reservoir geometry shows that Bravo field on rahman flank has high potential for development, thickening bed (high potential for sedimentation), and at several intervals it is seen development of subtidal channel and intertidal sand bar is very good. The lateral dimension of subtidal channel is about 3.5 km with a thicknees 10-25 ft, meanwhile intertidal sand bars have a laterlal dimension is 1-1.5 km with a thickness 0-10 ft, and sandy mud flat that have infinite dimension. The depositional direction is NE-SW, with Paleo-coastline bearing NW-SE, perpendicular to subtidal channel sand deposit. The facies that became the best reservoir in this research were Subtidal Channel and drilling at the Telisa Formation would be better to do horizontal drilling in order to generate economic value.